Rooting of semi-hardwood stem cuttings from current year shoots of Drymis brasiliensis - Luciele Milani Zem; Katia Christina Zuffellato-Ribas; Maria Izabel Radomski; Henrique Soares Koehler (Ciência Rural)
ABSTRACT: Drimys brasiliensis Miers is an Angiosperm native to the Atlantic Rainforest, commonly known as cataia. Because of dormancy of its seeds, due to embryonic immaturity, production of cataia seedlings presents challenges regarding propagation of the species. Thus, cuttings emerged as a possible technique to be applied, diminishing plants production time and ensuring uniformity of rooting. Stem cuttings from current year shoots were collected in autumn/2012, prepared with 10-12cm in length, a bevel cut on base and straight on top, keeping two leaves, one leaf or no leaves in the apical portion. After disinfestation, bases of cuttings were submitted to the following treatments with indole-3-butyric acid (IBA) in 50% hydro-alcoholic solution: 100% water, 0, 500, 1500, 3000, 4500 and 6000mg L-1 IBA. A completely randomized experimental design was used, with 3 types of cutting x 7 IBA concentrations, with four replicates of 10 cuttings per experimental unit. After 120 days, the variables percentage of rooted cuttings, number of roots per cutting, length of the three longest roots per cutting, percentage of cuttings with callus, alive and dead, with new shoots and the cuttings maintaining the original leaves were assessed. The application of IBA had no influence on any of the assessed variables. Cuttings with two leaves presented the best rooting percentage (51.1%) and the lowest mortality (5.4%), when compared to cuttings with one leaf (35.0%) or without leaves (0.4%). Cuttings without leaves are to be avoided, since they present the highest mortality percentage (93.6%).